Synthesis and evaluation of 1,3,5-triazine derivatives as sunscreens useful to prevent skin cancer - Reis, Juliana Santana [UNESP]; Corrêa, Marcos Antonio [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Dos Santos, Jean Leandro [UNESP] (Elsevier, 2019)
The incidence of skin cancers such as non-melanoma skin cancer and malignant melanoma has increased in the last few years mainly because of chronic exposure to ultraviolet (UV) radiation. Sunscreens protect the skin against harmful UV radiations; however, some limitations of these products justify the discovery of new UV filters. Novel 1,3,5-triazine derivatives (12a-h) obtained by the optimization of prototype resveratrol were synthesized and characterized. All compounds exhibited sun protection factor (SPF) and UVA protection factor (UVAPF) in the range of 3–17 and 3–13, respectively. These values were superior to resveratrol and the UV filter ethylhexyl triazone (EHT) currently available on the market. In addition, all compounds demonstrated in vitro antioxidant activity and thermal stability with the decomposition at temperatures above 236 °C. In conclusion, the novel 1,3,5-triazine derivatives have emerged as new UV filters with antioxidant effect useful to prevent skin cancer.
Keywords: 1,3,5-triazine; Antioxidant; EHT; Molecular optimization; Photoprotection; Skin cancer; Sunscreens; UV filters; UV radiation